Asymptotical investigations of the general distributions of the maxima and minima - Aksomaitis, Algimantas (Lietuvos matematikos rinkinys, 2000)
The convergence rate estimations in the limit theorem of the general distribution functions of the extreme values are presented. There results extend theoretical prepositions of the published work [3].